Investigation of soot formation of spark-ignited ethanol-blended gasoline sprays with single- and multi-component base fuels - Storch, Michael; Kögl, Matthias; Altenhoff, Michael; Will, Stefan; Zigan, Lars (Applied Energy, 2016)
Soot formation in DISI-(direct-injection spark-ignition) sprays is analyzed for ethanol-mixtures under stratified charge conditions. The investigation is conducted in a constant volume chamber (CVC), which is equipped with a spark ignition system. The operating conditions of the chamber are 0.8 MPa and 473 K. In previous studies, soot luminosity imaging indicated higher sooting tendencies for E20 (20 vol.% of ethanol in isooctane) sprays in comparison to pure isooctane and pure ethanol, however, no quantification of the soot distribution was possible. In this study, 2D laser-induced incandescence measurements (LII) in combination with laser extinction measurements (LEM) were performed for measurement of soot volume fraction distribution in the spray flame. The results show that soot is mainly formed in the spray front due to droplet combustion. Furthermore, soot volume fraction results confirm an increased sooting tendency of E20 compared to pure isooctane under the investigated conditions although the chemical properties of ethanol should reduce soot formation. This behavior can be explained by the delayed evaporation of E20 in comparison to isooctane due to physical fuel properties (mainly the enthalpy of evaporation), which are more important for soot formation especially at these short mixing times. Similar trends were found for the more complex multi-component fuel mixture isooctane-toluene (Tollso) and gasoline, both blended with 20 vol.% ethanol. Here, single combustion cycles were observed, where E20 exhibits higher. soot volume fraction. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: DISI; Ethanol-gasoline fuel blends; Toluene; Laser induced incandescence (LII); Laser extinction measurements (LEM)